Financial risk disclosure and financial attributes among publicly traded manufacturing companies evidence from Bangladesh - Ripon Kumar Dey; Syed Zabid Hossain; Zabihollah Rezaee (Journal of Risk and Financial Management, 2018)
We explore the relationship between the degree of financial risk disclosure and a firm's financial attributes. Financial risk disclosure indices (FRDIs) are calculated based on a set of 30 disclosure identifiers through content analysis of the annual reports of 48 manufacturing companies over a six-year period (2010-2015) in Bangladesh. We find no common practice among the companies in disclosing financial risk by integrating a customized financial risk disclosure into their financial reporting process. The results indicate that firm size, financial performance, and auditor type are positively and significantly associated with the level of financial risk disclosure.
Keywords: 330; financial risk; annual report; developing countries; financial attributes; Bangladesh